Hubungan Asupan Karbohidrat dan Lemak dengan Obesitas Sentral pada Karyawan Instansi di Kota Kendari - Nurali, Wa Ode; Tasnim, Tasnim; Sunarsih, Sunarsih (Jurnal Gizi Ilmiah, 2018)
The prevalence of central obesity has increased, especially in agency employees. Central obesity can cause heart disease, stroke and other degenerative diseases. This study aims to determine the relationship between carbohydrate intake and fat intake with central obesity in agency employees in Kendari City. This research is an analytic study with a cross sectional study design. The study was carried out on June 6-July 31 2018. The population was all employees at the Kendari City Agency in 2018 as many as 1,208 people and a sample of 90 people obtained by proportional random sampling. Data were processed using chi-square test, closeness test and logistic regression test. The results showed that the results of the chi-square test for the relationship between carbohydrate intake and central obesity obtained a p-value (0.000), for the relationship between fat intake and central obesity, a p-value (0.000) was obtained. The conclusion is that there is a relationship between carbohydrate intake, fat intake, fruit intake, vegetable intake, stress, knowledge and physical activity with central obesity and fat intake is the variable most associated with central obesity. It is recommended for the Provincial Health Office and the Kendari City Health Office to be able to determine policies on central obesity control for institutional employees in Kendari City. For institutional employees to regulate their diet by limiting carbohydrate and fat intake